Recent Advances in Ruthenium-Catalyzed Carbene/Alkyne Metathesis (CAM) Transformations - Padín, Damián; Varela, Jesús A.; Saá, Carlos (Synlett, 2020)
Carbene intermediates have shown versatile applications in modern synthetic chemistry. Catalytic ruthenium carbene/alkyne metathesis (CAM) with readily available substrates renders an efficient procedure for the in situ generation of ruthenium vinyl carbene intermediates. Here, recent advances in synthetic applications of ruthenium-catalyzed carbene/alkyne metathesis (CAM) are highlighted.1 Introduction2 Ruthenium Vinyl Carbenes through Carbene/Alkyne Metathesis (CAM)3 Nonpolar Transformations of Ruthenium Vinyl Carbenes4 Polar Transformations of Ruthenium Vinyl Carbenes4.1 Intramolecular Ruthenium-Catalyzed [1,5]- and [1,6]-Hydride Transfer/Cyclization4.2 Heterocyclizations of Alkynals and Alkynones4.3 Heterocyclizations of ortho-(Alkynyloxy)benzylamines5 DFT Studies on the Stereoselectivity of the CAM Reaction6 Conclusions
Keywords: alkynyl derivatives; carbenes; cyclization; heterocycles; metathesis; vinyl ruthenium carbenes